Central Europe and the Non-European World in the Long 19th Century - Křížová, Markéta; Malečková, Jitka (Frank & Timme, 2022)
Central Europe and the Non-European World in the Long 19th Century explores various ways in which inhabitants of the Austro-Hungarian Monarchy perceived and depicted the outside world during the era of European imperialism. Focusing particularly on the Czech Lands, Hungary, and Slovakia, with other nations as comparative examples, this collection shows how Central Europeans viewed other regions and their populations, from the Balkans and the Middle East to Africa, China, and America. Although the societies under Habsburg rule found themselves (with rare exceptions) outside the realm of colonialism, their inhabitants also engaged in colonial projects and benefited from these interactions. Rather than taking one "Central European" approach, the volume draws upon accounts not only by writers and travelers, but by painters, missionaries, and other observers, reflecting the diversity that characterized both the region itself and its views of non-Western cultures.